Factors predicting the outcome of allergen-specific nasal provocation test in children with grass pollen allergic rhinitis - Barreto, M.; Tripodi, S.; Arasi, S.; Landi, M.; Montesano, M.; Pelosi, S.; Potapova, E.; Sfika, I.; Villella, V.; Travaglini, A.; Brighetti, M. A.; Matricardi, P. M.; et al. (Frontiers in Allergy, 2023)
Background:Nasal provocation testing (NPT) is a reference methodology to identify the culprit allergen in patients with allergic rhinitis. Selecting the right allergen for NPT is particularly difficult in poly-sensitized patients with seasonal allergic rhinitis (SAR) Predictors of NPT’s outcome may facilitate the proper use of this test or even substitute it. Objective:To identify predictors of grass pollen NPT outcome among an array of clinical data, e-diary outcomes, and allergy test results in poly-sensitized pediatric SAR patients. Methods:Poly-sensitized, SAR patients with grass pollen allergy, from the @IT.2020 pilot project in Rome and Pordenone (Italy), participated in a baseline visit with questionnaires, skin prick testing (SPT), and blood sampling to measure total and specific IgE antibodies to grass pollen extracts and their major allergenic molecules. During the pollen season, patients filled the AllergyMonitor® e-diary app measuring their symptoms, medication intake, and allergy-related well-being via visual analogue scale (VAS). After the pollen season, patients answered clinical questionnaires and underwent a NPT with grass pollen extract. Results:We recruited 72 patients (age 14.3±2.8y, 46 males) sensitized to grass and/or other pollens, including olive (63; 87.5%) and pellitory (49; 68.1%). Patients positive to grass pollen NPT (61; 84.7%), compared to the negative ones, had worse VAS values in the e-diary, larger SPT wheal reactions, and higher IgE levels as well as specific activity to Timothy and Bermuda grass extracts, rPhl p 5 and nCyn d 1. Positive NPT to grass pollen was predicted by an index combining the specific activity of IgE towards Phl p 5 and Cyn d 1 (AUC 0.82; p<0.01; best cut-off ≥7.25%, sensitivity 70.5%, specificity: 90.9%). VAS results also predicted NPT positivity, although with less precision (AUC 0.77, p<0.01; best cut-off ≥7, sensitivity: 60.7%, specificity: 81.8%) Conclusions:An index combining the specific activity of IgE to rPhl p 5 and nCyn d 1 predicted with moderate sensitivity and high specificity the outcome of a grass pollen NPT in complex, poly-sensitized pediatric patients with seasonal allergic rhinitis. Further studies are needed to improve the index sensitivity and to assess its usefulness for NPT allergen selection or as an alternative to this demanding test procedure.